Spectral ripple discrimination in children with auditory processing disorder. (2nd November 2019) - Ankmnal Veeranna, Sangamanatha; Allan, Chris; Macpherson, Ewan; Allen, Prudence
Abstract: Objective: The purpose of this study was to examine developmental trends in spectral ripple discrimination (SRD) and to compare the performance of typically developing children to children with auditory processing disorder (APD). Study design: Cross-sectional study. Study sample: Fifteen children with APD, as well as 17 typically developing children and 14 adults reporting no listening or academic difficulties participated. Results: Typically developing children showed poor SRD thresholds compared to adults, indicating prolonged maturation of spectral shape recognition. Both typically developing children and APD children showed a maturational trend in SRD, but a General Linear Model fit to their thresholds showed that children with APD displayed SRD thresholds that were significantly poorer than those of typically developing children when controlling for age. This suggests that in APD children, SRD maturation lags behind typically developing children. Conclusion: Poor spectral ripple discrimination may explain some of the listening difficulties experienced by children with APD.